Micromachined high-g accelerometers : a review - Narasimhan, Vinayak (2015)
This Topical Review reviews research and commercial development of high-g micromachined accelerometers. Emphasis is placed on different high-g sensing schemes and popular design templates used to achieve high-g sensing. Additionally, trends in high-g micromachined accelerometer development both in research and in the market are discussed.